Acquired Ichthyosis Triggered by an Osseous Hemangiopericytoma: A Case Report and Review of the Literature - Aikaterini Patsatsi; Aikaterini Kyriakou; Vasilios Karavasilis; Fragkiski Tsatsou; Georgios Lazaridis; Dimitrios Kalabalikis; Dimitrios Sotiriadis (Karger Publishers, 2014)
Ichthyoses are a heterogeneous group of cutaneous keratinization disorders that can be congenital or acquired. Apart from neoplastic disorders, the acquired form of ichthyosis (AI) has been associated with a variety of diseases including infections, autoimmune/inflammatory and endocrine/metabolic diseases as well as nutritional conditions, medications and others. However, malignancy accounts for half of the reported cases, most commonly including lymphoproliferative disorders. We present a case of AI as a paraneoplastic skin manifestation of a primary, osseous hemangiopericytoma (HP) accompanied by multiple liver metastases. We also review the literature and discuss the necessity of investigating underlying diseases, especially malignancy, when adult-onset ichthyosis arises.